Perfeksionisme, Stres, dan Burnout Akademik pada Mahasiswa: Analisis Structural Equation Modeling - Eko Sujadi (Jurnal Counseling Care, 2023)
Academic burnout is a condition that should be avoided to prevent it from impeding students' academic achievement. This study aims to investigate the direct effects of perfectionism and academic stress on academic burnout and the role of academic stress as a mediator between perfectionism and academic burnout. One hundred Kartu Indonesia Pintar scholarship recipients (KIP-K) for the 2021 academic year voluntarily completed a questionnaire. The selection of respondents was based on the indication that KIP-K scholarship recipients were experiencing burnout due to high academic demands. Partial Least Squares Structural Equation Modeling was used for the analysis. The study's results showed a significant direct effect of perfectionism and academic stress on academic burnout. The results of indirect effect testing also revealed that academic stress provides a significant mediating effect between these relationships. These results show the importance of counseling services for students, particularly KIP-K scholarship recipients. In addition, it is necessary to evaluate flagship programs given to students to make them more suitable for their psychological abilities and conditions. Keywords: Perfectionism, Academic Stress, Academic Burnout